Pengembangan Media Pembelajaran Lift The Flap Book untuk Kemampuan Membaca Permulaan di Kelas I SDN 03 Tiumang - Apreasta, Lika; Anggrayni, M; Maimunah, Maimunah (Universitas Batanghari Jambi, 2024)
This research was motivated by the weak ability of students in learning activities, especially inreading. Based on the problems above, it is necessary to provide updated reading learning media that isinteresting and in accordance with the characteristics of first grade students, namely Lift The Flap Book, whichcan help students and teachers in the teaching and learning process. The development objective to be achievedin this research is to produce Lift The Flap Book learning media for beginning reading skills in grade Ielementary school that is valid, practical and effective. The model used in this development is a 4-D model. Themethod used in this research is Research and Development (R&D), which is a research method that aims toproduce certain products and test the validity and effectiveness of these products in their application. Theresults of the assessment of the Lift The Flap Book learning media validation sheet carried out by threevalidators produced an average score of 97.88% which was categorized as very valid. The results of theassessment sheet on the practicality of the Lift The Flap Book learning media produced an average score of90.62% which was categorized as very practical. and the results of the trial assessment of the Lift The FlapBook learning media carried out by 18 students produced an average of 90.07% which was categorized as veryeffective